Answer:
Option B. d = 5/3t
Step-by-step explanation:
see the attached figure to better understand the problem
we know that
A relationship between two variables, x, and y, represent a proportional variation if it can be expressed in the form [tex]y/x=k[/tex] or [tex]y=kx[/tex]
In a proportional relationship the constant of proportionality k is equal to the slope m of the line and the line passes through the origin
Let
d -----> the distance in meters
t ----> the time in seconds
Looking at the graph we have the point (3,5)
That means ----> For t=3 sec, d=5 m
Find the value of k
[tex]k=d/t[/tex]
substitute the value of y and the value of x
[tex]k=5/3[/tex]
The linear equation is
[tex]d=kt[/tex]
substitute the value of k
[tex]d=\frac{5}{3}t[/tex]
PLEASE HELP!!!
-x/4 - 2 = x + 1
Answer:
-x/4-3=x
Step-by-step explanation:
Answer:
-12/5
Step-by-step explanation:
-x/4-2=x+1
-x/4-x-2=1
-x/4-x=1+2
-x/4-x=3
-1/4x-4/4x=3
-5/4x=3
x=3/(-5/4)
x=(3/1)(-4/5)
x=-12/5
ill mark whoever answer this one first brainliest
Answer:
9/4 lbs (= 2 1/4 lbs)
Step-by-step explanation:
given original amount of chicken is 4 1/2 lbs ( = 9/2 lbs)
for half the recipe, we need half the amount of chicken
= 9/2 lbs x 1/2
= 9/4 lbs (= 2 1/4 lbs)
A dairy farmer ideally produces 800 gallons of milk per day. This total can fluctuate by as much as 40 gallons in either
direction. What is the maximum and minimum expected daily production?
What is the ratio of birds to eggs? Choose 1 answer: (Choice A) 3 :4, (Choice B) 4 :3 (Choice C) 3 :5 (Choice D) D 5 :3
Answer:
1 2/3 an egg to a bird
Step-by-step explanation:
because there are 5 eggs and divide 5 by 3 you get 1 2/3 and there are 3 birds so each gets 1 2/3rds an egg
Answer:
C) 3:5
Step-by-step explanation:
The question asks for the ratio of birds to eggs. It's asking how many birds there are in comparison to the number of eggs. The key to ratios is paying attention to which is listed first.
There are 3 birds, and 5 eggs, therefore the ratio is 3:5
Which answer is the explicit rule for the sequence 11,8.5,6,3.5,1
Answer: 3.5−2.5n
Explanation:
To find the common difference take the end term and subtract the first term:
8.5 -11 = -2.5
Take the third term and subtract the 3rd term to verify:
6-8.5 = -2.5 check
The formula for an arithmetic sequence is:
an = a1+d(n-1)
an = 11 -2.5(n-1)
Distribute:
an = 11 -2.5n+2.5
Combine terms:
answer = 13.5 - 2.5n
Explanation: Tread more on Brainly.com - https://brainly.com/question/13244259#read more find the common difference take the end term and subtract the first term:8.5 -11 = -2.5Take the third term and subtract the 3rd term to verify:6-8.5 = -2.5 check The formula for an arithmetic sequence is: an = a1+d(n-1)an = 11 -2.5(n-1)Distribute: an = 11 -2.5n+2.5Combine terms: answer = 13.5 - 2.5nAnswer:
Answer: 3.5−2.5n
A rectangle has an area of 90 square centimeters and a height of 12.5 centimeters. What is the length of the base?
Answer: l = 7.2
Step-by-step explanation:
90/12.5 = 7.2
7.2 * 12.5 = 90
Answer:
length of the rectangle is 7.2 centimeters.
Step-by-step explanation:
Area of the rectangle has been given as 90 square centimeters.
Height of the rectangle = 12.5 centimeters
Now we have to calculate the length of the rectangle.
Since, Area of the rectangle = Length × height
90 = 12.5 × length
Length = [tex]\frac{90}{12.5}[/tex]
= 7.2 centimeters
Therefore, length of the rectangle is 7.2 centimeters.
When solving p^2 + 5 = 8p - 7. Kate wrote p^2 + 12 = 8p. The property she used was:
1) the associative property
2) the commutative property
3) the distributive property
4) the addition property of equality
Answer:
4)
Step-by-step explanation:
Because they just added the same equality. And when you move the -7 over the equal sign it makes it positive so it would be p^2 + 5 + 7 = 8p and that makes it p^2 + 12 = 8p
The property used by the kate to write the function p^2 + 5 = 8p - 7 as p^2 + 12 = 8p is the addition property of equality.
Given to us
When solving p^2 + 5 = 8p - 7.
Kate wrote p^2 + 12 = 8p.
What property is used by Kate?As we can see Kate has simply added the number one, therefore, she had used the addition property of equality.
[tex]p^2 + 5 = 8p - 7\\\\p^2+5+7=8p\\\\p^2 + 12=8p[/tex]
Hence, the property used by the kate to write the function p^2 + 5 = 8p - 7 as p^2 + 12 = 8p is the addition property of equality.
Learn more about Addition property of equality:
https://brainly.com/question/13130806
remove all perfect squares from inside the square root
[tex] \sqrt{45} [/tex]
Answer:
3√5 or ≈6.7082
Step-by-step explanation:
1) √45
2) Factor out the perfect square: √3²×5
3) The root of a product is equal to the product of the roots of each factor: √3²√5
4) Reduce the index of the radical and exponent with 2: 3√5
5) Solution: 3√5 or ≈ 6.7082
after removing the perfect square factor from inside the square root of 45, we are left with 3√5.
To remove all perfect squares from inside the square root of √45, we need to factorize 45 and separate the perfect square factors.
The prime factorization of 45 is 3 × 3 × 5. Since 3 is repeated twice, it represents a perfect square factor.
We can rewrite the square root of 45 as the square root of (3 × 3 × 5). Using the property of square roots (√ab = √a × √b), we can simplify it as √(3 × 3) × √5.
The square root of 3 × 3 equals 3, so the expression simplifies to 3√5.
Therefore, after removing the perfect square factor from inside the square root of 45, we are left with 3√5.
Learn more about square root here
https://brainly.com/question/91924
#SPJ6
What is the length of bc?
Answer:
14.5
Step-by-step explanation:
Employ the SOH CAH TOA rule here.
So here you do Sin 65= x/16
solve for X you get 14.5
Use the quadratic formula to find both solutions to the quadratic equation
given below.
3x^2 - 7x - 1 = 0
which answers (in da pic)
HELP A BROTHA OUT!!!
The solutions to the quadratic equation 3x^2 - 7x - 1 = 0, using the quadratic formula, are x = [7 + sqrt(61)]/6 and x = [7 - sqrt(61)]/6.
Explanation:This question pertains to the solving of a quadratic equation using the quadratic formula. The quadratic formula is given by x = [-b ± sqrt(b^2 - 4ac)]/2a. In equation 3x^2 - 7x - 1 = 0, comparing it with the standard form of quadratic equation ax^2 + bx + c = 0, we can assign: a = 3, b = -7, and c = -1. Substituting these values into the formula, we get: x = [7 ± sqrt((-7)^2 - 4*3*(-1))]/2*3 = [7 ± sqrt(49 + 12)]/6 = [7 ± sqrt(61)]/6. So, the solutions to the equation are x = [7 + sqrt(61)]/6 and x = [7 - sqrt(61)]/6.
Learn more about Quadratic Equation here:https://brainly.com/question/30766352
#SPJ11
Find the next three terms of each sequence 60,52,44
Answer:
36, 28, 20
Step-by-step explanation:
To find the three terms of each sequence, simply subtract 8 from each number. For an example, you can notice the pattern by subracting 52 from 60. The answer I recieved was 8. That shows that the pattern is to subtract 8 from the following number.
Hope this helped :)
Answer:68
Step-by-step explanation:each is by 8 so add 8 onto each number to find the total
Is this mapping a function or not a function? Explain.
Yes, because the x-value 6 has two y-values paired with it.
No, because the x-value 6 has two y-values paired with it.
Yes, because each x-value has only one value paired with it.
No, because each x-value has only one y-value paired with it.
Answer:
a relation in which for every input there is exactly one output (for every x there is just one y)
Step-by-step explanation:
since you didn't give what was supposed to be a mapping function or not thats the best i can do
Which of the following fractions is equivalent to 4/20
A. 3/15
B. 2/12
C. 1/10
D. 3/19
Please answer QUICKLY.
3/15 is equivalent to 4/20
Mei and Anju are sitting next to each other on different horses on a carousel. Mei's horse is 3 meters from the center of the
carousel. Anju's horse is 2 meters from the center. After one rotation of the carousel, how many more meters has Mei
traveled than Anju?
Answer:
[tex]2\pi \approx 6.28\ meters[/tex]
Step-by-step explanation:
Mei's horse is 3 meters from the center of the carousel. After one rotation, Mei travelled
[tex]l_M=2\pi r=2\pi \cdot 3=6\pi\ meters[/tex]
Anju's horse is 2 meters from the center. After one rotation, Mei travelled
[tex]l_A=2\pi r=2\pi \cdot 2=4\pi\ meters[/tex]
The difference in their travelled distances is
[tex]l_M-l_A=6\pi -4\pi =2\pi \approx 6.28\ meters[/tex]
Mei travels 6.28 meters more than Anju in one rotation.
In one rotation, Mei's horse travels a distance of
2 * 3.14 * 3 = 18.84 meters.
In one rotation,
Anju's horse travels a distance of 2 * 3.14 * 2 = 12.56 meters.
Therefore, Mei travels 18.84 - 12.56 = 6.28 meters more than Anju in one rotation.
for such more question on distance
https://brainly.com/question/30395212
#SPJ3
Slope (-4,-3) (8,-9)
Answer: -1/2
as in negative one over two
Step-by-step explanation:
The graph of an equation is shown below:
Based on the graph, which of the following represents a solution to the equation?
A) (−2,−3)
B) (3, 1)
C) (1, 3)
D) (3, 2)
Runways A and B are parallel to each other and perpendicular to Runway C. If Runway D makes a 35 degree angle with Runway Aaa show in the diagram, what is the measure of the angle marked in the diagram between Runways C and D?
Answer:
55°
Step-by-step explanation:
Draw the diagram according to the given data (see attached diagram).
In this diagram,
line AC is runway A;line BD is runway B;line AB is runway C.Note that ∠GCH=35°
Angles GCH and CDI are corresponding angles. By corresponding angles postulate, angles GCH and CDI are congruent.
Angles CDI and BDE are vertical angles, so angles CDI and BDE are congruent as vertical angles.
Consider right triangle BDE. The sum of two acute angles of the right triangle is 90°, so
m∠BED=90°-m∠BDE
m∠BED=90°-35°=55°
solve the equation. 31-12n=211
Answer:
Step-by-step explanation:
31 - 12n = 21l Subtract 31 from both sides.
31-31-12n =211-31 Do the subtraction
-12n = 190 Divide by -12
-12n/-12 = 190/-12
n = -15.333333
79 plus what equals 90
Answer:
11
Step-by-step explanation:
90=79+x
-79-79
_________
11=x
Help math question theres a graph
dang this is hard for me, let me think
Angles a= 3x + 5 b= 5x - 18. C= 7x - 2
Answer:
x = 13.
So the 3 angles are a = 44, b = 47 and c = 89 degrees.
Step-by-step explanation:
If these are the angles are the 3 angles of a triangle they sum to 180 degrees, so:
3x + 5 + 5x - 18 + 7x - 2 = 180
15x - 15 = 180
15x = 195
x = 195/15
x = 13.
To find the values of angles a, b, and c given by the expressions 3x + 5, 5x - 18, and 7x - 2, we set up and solve equations involving these expressions. Once we find the value of x, we substitute it back into the expressions to find the angles.
Explanation:The question asks about angles given by the expressions a= 3x + 5, b= 5x - 18, and c= 7x - 2. In order to find the values of x and the corresponding values of angles a, b, and c, we need to set up and solve equations involving these expressions.
We can equate these expressions to given angles or to each other, and solve for x. Once we find the value of x, we can substitute it back into the expressions to find the angles.
For example, to find angle a, we substitute the value of x into the expression 3x + 5. Similarly, we substitute the value of x into the expressions 5x - 18 and 7x - 2 to find angles b and c, respectively.
Learn more about Angles here:https://brainly.com/question/13954458
#SPJ3
An app developer projects that he will earn 230$ for every 100 apps downloaded .which of the following equation can be used to be represented the proportional relationship between the number of apps ,x,and the total earnings
V
The developer would earn $50.00 if 20 apps are downloaded. Similarly, they can calculate earnings for any other number of app downloads using this equation.
To represent the proportional relationship between the total earnings (y) and the number of apps downloaded (x), we can use the formula for direct variation, which is:
[tex]\[ y = kx \][/tex]
Where:
- [tex]\( y \)[/tex] represents the total earnings,
- [tex]\( x \)[/tex] represents the number of apps downloaded, and
- [tex]\( k \)[/tex] is the constant of proportionality.
In this scenario, the app developer earns $20.00 for every 8 apps downloaded. This means that for every 8 apps downloaded, the earnings increase by $20.00. So, the constant of proportionality [tex](\( k \))[/tex] is the rate at which earnings increase per app downloaded.
To find the value of [tex]\( k \)[/tex], we can divide the total earnings by the number of apps downloaded:
[tex]\[ k = \frac{y}{x} \][/tex]
Given that the developer earns $20.00 for every 8 apps downloaded, we can substitute these values into the equation:
[tex]\[ k = \frac{20}{8} \][/tex]
[tex]\[ k = 2.5 \][/tex]
Now that we have the value of [tex]\( k \)[/tex], we can rewrite the equation with this value:
[tex]\[ y = 2.5x \][/tex]
This equation represents the proportional relationship between the total earnings [tex](\( y \))[/tex] and the number of apps downloaded [tex](\( x \))[/tex]. It shows that for every additional app downloaded, the total earnings increase by $2.50, maintaining a consistent rate of increase.
This equation allows the app developer to predict their earnings based on the number of apps downloaded. For example, if 20 apps are downloaded, the total earnings can be calculated as:
[tex]\[ y = 2.5 \times 20 = 50 \][/tex]
So, the developer would earn $50.00 if 20 apps are downloaded. Similarly, they can calculate earnings for any other number of app downloads using this equation.
In a sample of 94 widgets, 4 were defective. How many defective widgets would you expect in a sample of 282 widgets?
Answer:
12
Step-by-step explanation: 282 divided by 94 = 3
4x3=12
Answer:
12 defective widgets
Step-by-step explanation:
Here we calculate the "experimental probability:" 4 defective widgets out of 94 widgets comes out to a probability of being defective of 4/94, which of course could be reduced.
But we can go ahead and calculate the expected number of defective widgets by mult. that 282 widgets by the probability 4/94:
282 4
------- * ------- = 12
1 94
In this sample of 282 widgets, we could expect that 12 will be defective.
What property is (a•3)x b = b x(a•3) Using algebraic Expressions
Answer: Commutative Property of Multiplication
Step-by-step explanation:
Commutative property is when two terms trade places.
(a · 3) × b = b × (a · 3)
Notice that (a · 3) switched places with b
A large patio brick weighs 4 38 pounds. A small patio brick weighs 2 13 pounds.How much more does the large brick weighs
Answer:
2.25
Step-by-step explanation:
You have to subtract 2.13 from 4.38
Example: 4.38-2.13
Which point is an x-intercept of the quadratic function f(x) = (x – 4)(x + 2)?
Answer:
x = - 2, x = 4
Step-by-step explanation:
Given
f(x) = (x - 4)(x + 2)
To find the x- intercepts let f(x) = 0, that is
(x - 4)(x + 2) = 0 ← in standard form
Equate each factor to zero and solve for x
x - 4 = 0 ⇒ x = 4 → (4, 0 )
x + 2 = 0 ⇒ x = - 2 → (- 2, 0 )
Caroles age 8 years ago was 5 times carls age five years ago caroles age was 3 times carls age. How old is each now?
Answer:
(1) a+-+8+=+5%2A%28b+-+8%29
(1) a+-+8+=+5b+-+40
(1) 5b+-+a+=+32
and
(2) a+-+5+=+3%2A%28b+-+5%29
(2) a+-+5+=+3b+-+15
(2) 3b+-+a+=+10
Subtract (2) from (1)
(3) 2b+=+22
(3) b+=+11
Substitute this back in (1) or (2)
(1) 5%2A11+-+a+=+32
(1) a+=+55+-+32
(1) a+=+23
Carole is 23 and Carl is 11
Step-by-step explanation:
On a coordinate plane, square A B C D is shown. Point A is at (3, 4), point B is at (2, negative 2), point C is at (negative 4, negative 1), and point D is at (negative 3, 5). What is the perimeter of square ABCD? StartRoot 37 EndRoot units 4 StartRoot 37 EndRoot units 28 units 37 units
Answer:
4[tex]\sqrt{37}[/tex]
Step-by-step explanation:
Since the figure is a square, find the length of 1 side and multiply by 4 for perimeter.
Calculate the length of AB using the distance formula.
AB = √ (x₂ - x₁ )² + (y₂ - y₁ )²
with (x₁, y₁ ) = A(3, 4) and (x₂, y₂ ) = B(2, - 2)
AB = [tex]\sqrt{(2-3)^2+(-2-4)^2}[/tex]
= [tex]\sqrt{(-1)^2+(-6)^2}[/tex]
= [tex]\sqrt{1+36}[/tex]
= [tex]\sqrt{37}[/tex]
Hence
perimeter = 4AB = 4[tex]\sqrt{37}[/tex]
Answer:
4 root 37units
Step-by-step explanation:
gl on the exam
Julio wants to calculate 200,000 300,000. When he used
his calculator to multiply, it showed the result below:
6E-10
Write the number shown on the calculator display in
standard form
OA) 60,466,176
OB) 600,000,000
OC) 6,000,000,000
OD) 60,000,000,000
Answer:
D = 60,000,000,000
Step-by-step explanation:
When "E" appears on a calculator , it means exponential and it is used to denote numbers that are too big or small to appear on the calculator screen in their decimal form.
Therefore 6E-10 means 6 exponential 10 , mathematically written as 6^10
which is 60,000,000,000
F(x) = 3x - 7 and g(x) = -2x - 6. Find (f + g)(x). Show steps.
Answer:
x - 1
Step-by-step explanation:
(f + g)(x)=f(x) + g(x)
(f + g)(x)=(3x - 7) + (-2x - 6)
(f + g)(x)= 3x - 7 - 2x + 6
(f + g)(x)= 3x - 2x - 7 + 6
(f + g)(x)= x -1